2006
DOI: 10.4314/njphy.v17i1.38001
|View full text |Cite
|
Sign up to set email alerts
|

Studies on relaxation length of wood by method of gamma radiation

Abstract: Relaxation lengths and half-thickness values of different types of wood were determined using gamma radiation from 60 C0 source. Results show that oxystigma (Oxystima spp) has the highest relaxation length of 23.810cm, while mangrove (Rhizoohora spp) has the least relaxation length of 1.247 cm. Results also show that Oxystima (Oxystima spp) has the highest half thickness value of 16.500 cm and Mangrove (Rhizophora spp) has the least half-thickness value of 0.864 cm. Two mathematical models have been developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The BIR measured at Okpoto and Nteze are in tendem with recommended value of 0.013mR/h. Akpabio et al [10] also studied "the environmental radioactive levels in Ikot-Ekpene and reported that the radioactivity levels in the area is generally low ranging". "High radiation levels and doses are detrimental to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The BIR measured at Okpoto and Nteze are in tendem with recommended value of 0.013mR/h. Akpabio et al [10] also studied "the environmental radioactive levels in Ikot-Ekpene and reported that the radioactivity levels in the area is generally low ranging". "High radiation levels and doses are detrimental to human health.…”
Section: Introductionmentioning
confidence: 99%
“…For the instance, it is key input for estimating potential evapotranspiration which play a major role in the design of water supply storage reservoirs and irrigation systems. Inspite of the importance of global solar radiation data, its measurements is not frequently available especially in the developing countries like Nepal 6 .…”
Section: Introductionmentioning
confidence: 99%